Beach Forest Communities of San Agustin, Romblon with Notes on Coastal Threats - Gonzalez, Jeric; Mazo, Xyrra Jeremiah; Mangao, Shiela Me (Romblon State University Research Journal, 2022)
The coastal plains of the Philippines were among the first sites opened for human settlement. However, the sprouting of communities has displaced beach forests and mangrove swamps. The growing intensity and frequency of weather disturbances brought by changing global climate highlight beach forests' critical role as bio-shields for vulnerable coastal communities. Unfortunately, beach forests continue to disappear due mainly to conversion into human settlements and wanton harvesting for fuel wood and medicinal plant parts. Currently, no study has been conducted on the beach forest communities in San Agustin, Romblon; thus, this study was conceptualized. A survey was conducted in all barangays of San Agustin, and species identification was made. A total of 38 species of beach forest plants belonging to 21 families were identified. The municipality of San Agustin has a species richness of 3.99, Shannon diversity index of 2.53, Simpson dominance index of 8.73, and Evenness index of 0.70. Cabolutan had the highest species richness among the barangays, while Binonga-an had the highest diversity and dominance index. The relatively high abundance of Cocos nucifera denotes that these areas were subjected to anthropogenic activities. Erosion, garbage, seawall, road widening, and infrastructure developments for beach resorts and summer houses were the five major coastal threats recorded in the beach forest areas around San Agustin, Romblon. These data can serve as a reference for different conservation activities to protect and enhance the current status of the beach forest of San Agustin, Romblon.